Long-Term Sequelae and Health-Related Quality of Life Associated With Lyme Disease: A Systematic Review. (27th November 2019) - Mac, Stephen; Bahia, Simran; Simbulan, Frances; Pullenayegum, Eleanor M; Evans, Gerald A; Patel, Samir N; Sander, Beate
Abstract: Lyme disease (LD) is the most commonly reported vector-borne disease, but its clinical consequences remain uncertain. We conducted a systematic review of the long-term sequelae and health-related quality of life (HRQoL) associated with LD in North America and Europe. We performed searches in 6 electronic databases up to December 2018 following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, including observational studies reporting long-term sequelae, HRQoL, and prognostic factors. We included 46 studies, published between 1994 and 2019. Based on 21 studies reporting attributable outcomes, higher proportions of sequelae reported from exposed patients were: neck pain, myalgia, arthralgia, paresthesia, sleep disorder, poor appetite, and concentration difficulties. Patients with PTLDS reported impaired HRQoL compared to the general US population. Included studies were highly heterogeneous in terms of study design, settings, patient characteristics, and quality. Patients with LD are more likely to report nonspecific long-term sequelae, especially those experiencing persistent symptoms posttreatment. Opportunities exist for prospective longitudinal studies to better understand LD outcomes. Abstract : This systematic review summarizes the long-term consequences and quality-of-life associated with Lyme disease (LD) after treatment compared to normal populations. Nonspecific patient-reported symptoms are more common in patients with LD and posttreatment Lyme disease syndrome than in controls.